If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying in(x + -2) + in(2x + -3) = 2inx Reorder the terms: in(-2 + x) + in(2x + -3) = 2inx (-2 * in + x * in) + in(2x + -3) = 2inx (-2in + inx) + in(2x + -3) = 2inx Reorder the terms: -2in + inx + in(-3 + 2x) = 2inx -2in + inx + (-3 * in + 2x * in) = 2inx -2in + inx + (-3in + 2inx) = 2inx Reorder the terms: -2in + -3in + inx + 2inx = 2inx Combine like terms: -2in + -3in = -5in -5in + inx + 2inx = 2inx Combine like terms: inx + 2inx = 3inx -5in + 3inx = 2inx Solving -5in + 3inx = 2inx Solving for variable 'i'. Move all terms containing i to the left, all other terms to the right. Add '-2inx' to each side of the equation. -5in + 3inx + -2inx = 2inx + -2inx Combine like terms: 3inx + -2inx = 1inx -5in + 1inx = 2inx + -2inx Combine like terms: 2inx + -2inx = 0 -5in + 1inx = 0 Factor out the Greatest Common Factor (GCF), 'in'. in(-5 + x) = 0Subproblem 1
Set the factor 'in' equal to zero and attempt to solve: Simplifying in = 0 Solving in = 0 Move all terms containing i to the left, all other terms to the right. Simplifying in = 0 The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined.Subproblem 2
Set the factor '(-5 + x)' equal to zero and attempt to solve: Simplifying -5 + x = 0 Solving -5 + x = 0 Move all terms containing i to the left, all other terms to the right. Add '5' to each side of the equation. -5 + 5 + x = 0 + 5 Combine like terms: -5 + 5 = 0 0 + x = 0 + 5 x = 0 + 5 Combine like terms: 0 + 5 = 5 x = 5 Add '-1x' to each side of the equation. x + -1x = 5 + -1x Combine like terms: x + -1x = 0 0 = 5 + -1x Simplifying 0 = 5 + -1x The solution to this equation could not be determined. This subproblem is being ignored because a solution could not be determined. The solution to this equation could not be determined.
| 3x-10=-6x+35 | | Y-1/2+4g-z+3z-1/9 | | 12/x=6 | | -7(x+1)=3 | | x-8=-x-8 | | (5x+6)-9=24 | | 5(x-10)=45 | | 2x-9=x+1 | | t/12=900/30 | | 4(n+1)=2n-2 | | 1/2x+6=5 | | -60z^5+85z^4+25z^3= | | 6x+4=-16+2x | | 18+x=25 | | 8t-28=5t-7 | | 7.9x=11.85 | | 4/5y=-3/6 | | 23.7=3.5b | | [x-1]=2014 | | 40/x=5 | | 9-2x=x+1 | | -1/3x=-1/6 | | 12+5m=8m | | (12x-6y)(1/2x+3/2y) | | 14+x=23 | | x-10=6x-60 | | 3x=36-(6x+54) | | 3x=6-(6x+54) | | -7x+1=-34 | | -3x-1=-x+5 | | 104/20= | | 10=6a+-9a+a |